Local Treatment of Unresectable Colorectal Liver Metastases: Results of a Randomized Phase II Trial. (17th March 2017) - Ruers, Theo; Van Coevorden, Frits; Punt, Cornelis J A; Pierie, Jean-Pierre E N; Borel-Rinkes, Inne; Ledermann, Jonathan A; Poston, Graeme; Bechstein, Wolf; Lentz, Marie-Ange; Mauer, Murielle; Folprecht, Gunnar; Van Cutsem, Eric; et al.
Abstract: Background: Tumor ablation is often employed for unresectable colorectal liver metastases. However, no survival benefit hasever been demonstrated in prospective randomized studies. Here, we investigate the long-term benefits of such an aggressive approach. Methods: In this randomized phase II trial, 119 patients with unresectable colorectal liver metastases (n < 10 and no extrahepatic disease) received systemic treatment alone or systemic treatment plus aggressive local treatment by radiofrequency ablation ± resection. Previously, we reported that the primary end point (30-month overall survival [OS] > 38%) was met. We now report on long-term OS results. All statistical tests were two-sided. The analyses were according to intention to treat. Results: At a median follow up of 9.7 years, 92 of 119 (77.3%) patients had died: 39 of 60 (65.0%) in the combined modality arm and 53 of 59 (89.8%) in the systemic treatment arm. Almost all patients died of progressive disease (35 patients in the combined modality arm, 49 patients in the systemic treatment arm). There was a statistically significant difference in OS in favor of the combined modality arm (hazard ratio [HR] = 0.58, 95% confidence interval [CI] = 0.38 to 0.88, P = .01). Three-, five-, and eight-year OS were 56.9% (95% CI = 43.3% to 68.5%), 43.1% (95% CI = 30.3% to 55.3%), 35.9% (95% CI = 23.8% to 48.2%), respectively, in the combined modality arm and 55.2% (95% CI = 41.6% to 66.9%), 30.3% (95% CI = 19.0% to 42.4%), 8.9% (95% CI = 3.3% to 18.1%), respectively, in the systemic treatment arm. Median OS was 45.6 months (95% CI = 30.3 to 67.8 months) in the combined modality arm vs 40.5 months (95% CI = 27.5 to 47.7 months) in the systemic treatment arm. Conclusions: This phase II trial is the first randomized study demonstrating that aggressive local treatment can prolong OS in patients with unresectable colorectal liver metastases.